Did the prevalence of suprascapular neuropathy in professional volleyball players decrease with the changes occurred in serving technique? - Mazza, D.; Iorio, R.; Drogo, P.; Gaj, E.; Viglietta, E.; Rossi, G.; Monaco, E.; Ferretti, A. (The Physician and Sportsmedicine, 2021)
Objectives: Suprascapular neuropathy is more frequent in volleyball as compared to other overhead sports. This study aims to report the actual prevalence of suprascapular neuropathy among elite volleyball players. The hypothesis is that becoming jump topspin serves the most common serving technique, suprascapular neuropathy reduced its frequency.